RANCANG BANGUN ALAT MONITORING PERGERAKAN TARUNA PADA SAAT MELAKSANAKAN LATIHAN - Widodo, Slamet; Hifni, Muchammad (PPM Sdirjianbang Akademi Militer, 2023)
The movement of cadets needs to be monitored because it is one of the benchmarks of the seriousness of the cadets in every outdoor exercise carried out in the field. It is also an evaluation material in every outdoor exercise carried out in the field. The goal is that the implementation of outdoor exercises carried out in the field can be achieved. Therefore, a tool is needed that can monitor the movement of ATMega 16 microcontroller-based cadets. Therefore, it is necessary to design a cadet movement monitoring tool when carrying out microcontroller-based outdoor training combined with GPS as a marking position and assisted by RF YS 1020 The microcontroller as a sender and receiver of coordinate data position. The goal is that the author can design and make ATMega 16-based cadet movement monitoring tools as well as design and manufacture interfaces on a computer/laptop using the Delphi language. The ATMega 16 microcontroller-based cadet movement monitoring tool uses the EM411 GPS module as a provider of cadet coordinate position data via serial communication. The tool can work well and the interface on a computer/laptop using the Delphi 7 language with additional comport objects to process serial data from the RF YS 1020 and is depicted on Google Map can be operated properly.